SF038/#1037 Splenic mobilization and resections in cytoreductive surgery for ovarian cancer. (4th December 2022) - Lucena, Claudio; Lyria, Rossini; Fernandes, Pedro Henrique; Bomfati, Fernanda; Ribeiro, Reitan; Linhares, José; Wilczek, Eduardo; Tsunoda, Audrey
Abstract : Introduction: More than 60% of all ovarian cancer patients are diagnosed in stages III and IV (FIGO 2018) (1). The vast majority will present upper abdominal disease, with splenic capsule, hilum or even parenchyma involvement. In this scenario, surgical techniques addressing partial or total splenectomy becomes an essential part of a complete cytoreductive surgery. Description: This video demonstrates surgical techniques using routine materials for implants resection in the spleen, including partial and total splenectomy. The combination of preoperative imaging and surgical Peritoneal Carcinomatosis Index (PCI) evaluations may predict the precise technique indication. A posterior organ approach allows access to the splenocolic, splenophrenic, and splenorenal ligaments, which are identified and divided. Ligation of the short gastric vessels can be achieved with metallic clips or silk stitches. During a total resection due to parenchymal metastasis, dissection of the splenic hilum with ligation of the splenic artery followed by the splenic vein. We demonstrate two other cases with partial/capsular splenectomy with electrocautery and/or cold blade. Temporary clipping of the splenic vessels may be necessary for extended partial splenectomies, and will be described in another video. Conclusion/Implications: This video demonstrates reproducible standardized techinques for total or partial splenectomy in ovarian cancer cytoreduction.